Pengaruh Media Geoboard terhadap Kemampuan Menghitung Keliling Bangun Datar di Sanggar Belajar Kampung Bharu Malaysia - Riri Damayanti; Ismail Saleh Nasution (LPPM Institut Pendidikan Nusantara Global, 2026)
Geoboard learning media is a visual and manipulative tool that is effectively used in mathematics learning, especially on the material of the perimeter of flat shapes at the elementary school level. This study aims to determine the effect of using geoboard media on students' ability to calculate the perimeter of flat shapes at the Kampung Bharu Malaysia Guidance Center. The study used a quantitative approach with a pre-test and post-test experimental design. The research sample consisted of 9 fourth-grade students. Data were collected through tests on the ability to calculate the perimeter of flat shapes, observations, interviews, and documentation. The results of the study showed a significant increase in students' abilities after the application of geoboard media, indicated by a significant difference in pre-test and post-test scores based on a paired t-test (Sig. 0.000 < 0.05). Geoboard media helps students understand the concept of side length, the shape of flat shapes, and the procedure for calculating the perimeter in a concrete and visual way, so that learning becomes more interactive and meaningful. Thus, it can be concluded that the use of geoboard media has a positive and significant effect on improving the ability to calculate the perimeter of flat shapes.